2007
DOI: 10.1111/j.1741-3737.2007.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Gay Men: Negotiating Procreative, Father, and Family Identities

Abstract: Our qualitative study examines the social psychology of gay men’s experiences with their procreative, father, and family identities. In‐depth interviews were conducted with 19 childless gay men and 20 gay men in the United States who have fathered using diverse means excluding heterosexual intercourse. By focusing on men aged 19 – 55 residing primarily in Florida and New York, our novel analysis illuminates how emerging structural opportunities and shifting constraints shape gay men’s procreative consciousness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
178
0
33

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(219 citation statements)
references
References 18 publications
8
178
0
33
Order By: Relevance
“…Thus Bauermeister argues that legal inequalities can hinder the potential for gay and bisexual men to be able to realize their goal of becoming parents. These findings resonate with the findings from Berkowitz and Marsiglio's (2007) study focused on gay men. Analyzing data from 39 interviews (19 of which were with childless gay men), they found that legal context shapes gay men's interpretations about whether or not they can become parents.…”
Section: Desiring Parenthoodsupporting
confidence: 50%
See 1 more Smart Citation
“…Thus Bauermeister argues that legal inequalities can hinder the potential for gay and bisexual men to be able to realize their goal of becoming parents. These findings resonate with the findings from Berkowitz and Marsiglio's (2007) study focused on gay men. Analyzing data from 39 interviews (19 of which were with childless gay men), they found that legal context shapes gay men's interpretations about whether or not they can become parents.…”
Section: Desiring Parenthoodsupporting
confidence: 50%
“…Historically, being a LGBQ individual and being a parent was seen as a contradiction (Berkowitz 2007;Berkowitz and Marsiglio 2007;Bozett 1989;Kazyak et al 2014;Lewin 2009;Mallon 2004;Stacey 2011;Tasker and Patterson 2007). Many sexual minority individuals who were parents became parents before coming out and/or in the context of different-sex relationships (e.g., Bozett 1989;Mezey 2015).…”
Section: Background: Lgbq Parents and The Lawmentioning
confidence: 99%
“…Taip gyvenantys asmenys, pasak autoriaus, gali būti neblogai prisitaikę prie savo aplinkos, kad išėjimą į viešumą (atsiskleidimą) interpretuoja kaip ne tokį reikšmingą dalyką savo gyvenime ir būna mažiau motyvuoti atsiskleisti savo aplinkoje. (Berkowitz, Marsiglio 2007). Vėliau, pasak tyrėjų, kai vyrai sutikdavo draugų, turinčių vaikų, pavyzdžiui, lesbietes mamas, prižiūrėdavo kitų vaikus ar dirbdavo savanoriais su vaikais, keitėsi ir jų pačių supratimas.…”
Section: Kultūra Ir Visuomenė Socialinių Tyrimų žUrnalas   ()unclassified
“…Kaip pabrėžia autoriai (Berkowitz, Marsiglio 2007;Golberg 2012), kaip tik ilgalaikių santykių stabilumas leidžia planuoti vaikus. Penki tyrimo dalyviai per interviu turėjo ilgalaikius partnerius, jų santykių trukmė svyravo nuo metų iki trejų.…”
Section: Aš Tiesiog Pasakiau Besėdint Mums Bešnekant Bet Jinai Negerunclassified
See 1 more Smart Citation